Stachytine Hydrochloride Improves Cardiac Function in Mice with ISO-Induced Heart Failure by Inhibiting the α-1,6-Fucosylation on N-Glycosylation of β1AR - Hu, Panwei; Guo, Shuting; Yang, Songru; Wang, Sining; Wang, Sai; Shan, Xiaoli; Zhao, Pei; Guo, Wei; Xu, Ming; Zhang, Chen; Lu, Rong; Chen, Huihua (Frontiers in Pharmacology, 2022)
Abstract: Background: Cardiovascular diseases have become a major public health problem that seriously threatens human health. The cumulative effects of various cardiovascular events will eventually develop into chronic heart insufficiency and even heart failure, and the β1 adrenergic receptors signal pathway plays an important role in this process. Stachytine hydrochloride is the main active ingredient of Yimucao, which is a traditional Chinese medicine used to treat gynecological diseases. Modern studies have found that stachytine hydrochloride has a good cardioprotective effect, but it is still unclear whether stachytine hydrochloride has effect on the β1 adrenergic receptors signal pathway. The purpose of this study is to explore the effect of stachytine hydrochloride on β1 adrenergic receptors signal pathway. Method: In this study, a continuous infusion of isoproterenol (40mg/kg/d) was administered to mice and ventricular myocytes explored the potential mechanism of stachytine hydrochloride (12 mg/kg/d) on the β1 adrenergic receptors signal pathway in the heart. Evaluate changes in cardiac morphology and function by echocardiography, cardiac hemodynamics, and histological methods, and detect molecular changes by Western blot and immunofluorescence. Treatment of primary cultured adult mouse or neonatal rat ventricular myocytes with or without isoproterenol (10-7 M), PNGase F (10-2 units/ml) and stachytine hydrochloride (10-5 M) at different time points, Detect α-1,6- fucosylation on N-glycosylation, calcium transient, contraction and relaxation function and related signals. Results: Stachytine hydrochloride reduces cardiac remodeling and modulates hemodynamic parameters during chronic β1 adrenergic receptors activation in vivo. The N-glycosylation of β1 adrenergic receptors decreased after continuous isoproterenol stimulation, while stachytine hydrochloride can increase the N-glycosylation of β1AR in the heart of mice with isoproterenol-induced heart failure. Decreased N-glycosylation of β1 adrenergic receptors will down-regulate cAMP/PKA signal pathway and inhibit myocardial excitation and contraction coupling. Stachytine hydrochloride significantly reduced isoproterenol-induced cardiac N-linked glycoproteins with α-1,6- fucosylation. Conclusion: Our results show that stachytine hydrochloride inhibits the synthesis of α-1,6-fucosylation on the N-terminal sugar chain by reducingα-1,6-fucosyltransferase (FUT8), and α-1,3-mannosyl-glycoprotein 4-β-N-acetylglucosaminyltransferase A (MGAT4a), up-regulating the N-glycosylation level on β1 adrenergic receptors, and maintaining cAMP/PKA signal pathway activation.